IJARAH ASSET CONTRACT: A PRODUCT INNOVATION FOR ISLAMIC MICROFINANCE - Umrotul Khasanah; Ahmad Tibrizi Soni Wicaksono; Alvi Rahmawati (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
This research aims to develop a tool for assessing the potential of ijarah asset contract model as a product offered by Islamic Microfinance Institutions (IMFIs) to Micro, Small and Medium Enterprises (MSMEs) in Malang Regency, Batu City, and Malang City areas of Indonesia. In this context, a grounded theory is applied, including open, axial, and selective coding, as well as qualitative model analysis to report crucial factors for ijarah asset contract product at IMFIs. The results show that Sharia compliance is the most fundamental instrument, followed by trust, benefit, agreement, and tolerance based on the priority criteria. In addition, the relationship between instruments create the best implementation model in the forerunner of ijarah asset contract product. This research is carried out by determining the instrument of ijarah asset contract and explaining the relationship between instruments forming an implementation model. The development of fresh ijarah product innovations at IMFIs is conducted to facilitate asset leasing for MSMEs. A model is also proposed using the results as a benchmark for execution to minimize the potential for unsuccessful outcomes.